Characterization of Crilin and Nanocurcumin’s Synergistic Effect on Treatment for 7.12-Dimethylbenz[a]anthracene (DMBA)-Induced Breast Cancer Mice - Buu, Tran Gia; Nhung, Tran Thi Phuong; Trang, Nguyen Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 1, 2018)
Breast cancer is the neoplastic disease which is characterized by unregulated ductal and lobular hyperplasia. Some herbal remedies have proved the inhibitory effect on breast cancer, such as crilin-extracted from Cirnum latifolum and curcumin-isolated from Cucuma longa . However, the synergistic effect of crilin and nanocurcumin has not been studied so far. In this study, we established the mouse model of breast cancer induced by DMBA and evaluated the effectiveness of the combination of crilin and nanocurcumin in treatment of breast cancer. After a 12-week co-administration of crilin and nanocurcumin, the DMBA-induced mice’s body weight and the number of erythrocytes and leukocytes in their blood reversed. Furthermore, the synergistic effect of crilin and nanocucumin on reduction in the tumor volume was proven. Histological analysis revealed that co-administration of crilin and nanocurcumin inhibited the expansion of mammary ductal carcinoma cells into surrounding tissues, recovered lobular cells structure, and diminished leukocyte composition. Thereby, the combination of crilin and nanocurcumin helped recover immune system and prevent further development of breast cancer. Keywords Breast cancer, DMBA, Cirnum latifolum, nanocucumin, synergistic effect. References [1] J. Ferlay, C. Héry, P. Autier, R. Sankaranarayanan, Global Burden of Breast Cancer, In: C. Li (eds) Breast Cancer Epidemiology, Springer, New York, 2010. [2] J. Vinodhini and S. Sudha, Effect of bis-carboxy ethyl germanium sesquoxide on n-nitroso-n-methylurea-induced rat mammary carcinoma, Asian Journal of Pharmaceutical and Clinical Research 6 (2013) 239. [3] F. Atashrazm, R.M. Lowenthal, G.M. Woods, A.F. Holloway, J.L. Dickinson, Fucoidan and Cancer: A Multifunctional Molecule with Anti-Tumor Potential, Marine Drugs, 13 (2015) 2327. [4] M. Jenny, A. Wondrak, E. Zvetkova E, N.T.N. Tram, P.T.P. Phi, H. Schennach, Z Culig, F. Ueberall, D. Fuchs, Crinum Latifolium Leave Extracts Suppress Immune Activation Cascades in Peripheral Blood Mononuclear Cells and Proliferation of Prostate Tumor Cells, Scientia Pharmaceutica, 79 (2011) 323. [5] H.Y. Nguyen, B.H. Vo, L.T. Nguyen, J. Bernad, M. Alaeddine, A. Coste, K. Reybier, B. Pipy, F. Nepveu, Extracts of Crinum latifolium inhibit the cell viability of mouse lymphoma cell line EL4 and induce activation of anti-tumour activity of macrophages in vitro, Journal of Ethnopharmacology, 149 (2013) 75. [6] A.S. Darvesh, B.B. Aggarwal, A. Bishayee, Curcumin and Liver Cancer: A Review, Current Pharmaceutical Biotechnology, 13 (2012) 218. [7] M.H. Khosropanah, A. Dinarvand, A. Nezhadhosseini, A. Haghighi, S. Hashemi, F. Nirouzad, S. Khatamsaz, M. Entezari, M. Hashemi, H. Dehghani, Analysis of the Antiproliferative Effects of Curcumin and Nanocurcumin in MDA-MB231 as a Breast Cancer Cell Line, Iranian Journal of Pharmaceutical Research, 15 (2016) 231. [8] F. Milano, L. Mari L, W. van de Luijtgaarden, K, Parikh, S. Calpe, K.K. Krishnadath, (2013) Nano-curcumin inhibits proliferation of esophageal adenocarcinoma cells and enhances the T cell mediated immune response, Front. Oncol., 3 (2013) 137. [9] T.T. Do, P.T. Do, C.T. Nguyen, N.T. Nguyen, T.T. Nguyen. Experimental tumorization on mice by DMBA (7,12 Dimethyl Benz[A] Anthracen) VNU Journal of Science-Natural Science and Technology, 25 (2009) 107. (in Vietnamese) [10] A. Faustino-Rocha, P.A. Oliveira , J. Pinho-Oliveira,C. Teixeira-Guedes, R. Soares-Maia, R.G. da Costa, B. Colaço, M.J. Pires, J. Colaço, R. Ferreira, M. Ginja, Estimation of rat mammary tumor volume using caliper and ultrasonography measurements, Lab Anim (NY) 42 (2013) 217. [11] C.H. Chen, S.H. Wu, Y.M. Tseng, J.B. Liao, H.T. Fu, S.M. Tsai, L.Y. Tsai, Suppressive Effects of Puerariae Radix on the Breast Tumor Incidence in Rats Treated with DMBA, Journal of Agricultural Science, 9 (2017) 68. [12] M. Fatemi and F. Ghandehari, F, The effect of Ficus carica latex on 7, 12-dimethylbenz (a) anthracene-induced breast cancer in rats, Avicenna Journal of Phytomedicine, in press (2017), 1. [13] S. Bimonte, A. Barbieri, G. Palma, A. Luciano, D. Rea, C Arra, Curcumin Inhibits Tumor Growth and Angiogenesis in an Orthotopic Mouse Model of Human Pancreatic Cancer, BioMed Res. Int., 2013 (2013) 810423. [14] M. Xue, Y. Ge, J. Zhang, Q. Wang, L. Hou, Y. Liu, L. Sun, Q. Li. Anticancer Properties and Mechanisms of Fucoidan on Mouse Breast Cancer In Vitro and In Vivo, PLoS ONE, 7 (2012) e43483. [15] Z.D. Lv, X.P. Liu, W.J. Zhao, Q. Dong, F.N. Li, H.B. Wang, B. Kong, B, Curcumin induces apoptosis in breast cancer cells and inhibits tumor growth in vitro and in vivo. International Journal of Clinical and Experimental Pathology, 7 (2014) 2818. [16] J.E. Pizzorno, M.T. Murray, H. Joiner-Bey, The Clinician's Handbook of Natural Medicine E-Book, Elsevier Health Sciences Publisher, Amsterdam, 2016.   n vitro and in vivo. International Journal of Clinical and Experimental Pathology, 7 (2014) 2818. [16] J.E. Pizzorno, M.T. Murray, H. Joiner-Bey, The Clinician's Handbook of Natural Medicine E-Book, Elsevier